Islamic theology on human creation: Relevance to education and challenges in the global era - Ismail Ismail; Masganti Sitorus; Muhammad Abrar Parinduri (Jurnal Sinar Edukasi, 2025)
The study explores the concept of human creation within the framework of Islamic theology and education and its implications for achieving maqasid al-shariah. Using a qualitative approach, this research combines literature analysis and field data through semi-structured interviews, observations, and document analysis in Islamic senior high schools in North Sumatra, Indonesia. Primary sources such as the Qur'an and Hadith, as well as classical and contemporary scholarly works, are examined to understand the spiritual, moral, and social dimensions of human creation. The findings show that the concept of human as ahsani taqwim and khalifah on earth not only confirms human dignity and the sanctity of life, but also supports the five main objectives of maqasid al-shariah: protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-‘aql), progeny (hifz al-nasl), and wealth (hifz al-mal). The integration of theological insights into Islamic education through discussion-based learning, social projects, and guided personal reflection effectively helps students internalize Islamic values, enhance spiritual awareness, and build strong moral character. This concept is also relevant to contemporary issues—such as bioethics, environmental degradation, and moral decline—by offering a comprehensive Islamic ethical framework. The study recommends curriculum development that integrates theological values, community engagement through collaborative educational programs, and policy formulation that harmonizes scientific advancement with Islamic principles, thereby strengthening maqasid-based Islamic education in facing global challenges.